Highly selective uptake of carbon dioxide on the zeolite |Na10.2KCs0.8|-LTA – a possible sorbent for biogas upgrading. Issue 24 (2nd June 2016) - Cheung, Ocean; Wardecki, Dariusz; Bacsik, Zoltán; Vasiliev, Petr; McCusker, Lynne B.; Hedin, Niklas
Abstract : Zeolite |Na10.2 KCs0.8 |-LTA was found to be a promising adsorbent for applications such as biogas upgrading. The CO2 -over-CH4 selectivity was very high (over 1500). Abstract : The|Na10.2 KCs0.8 |8 [Al12 Si12 O48 ]8 ( Fm 3̄ c )-LTA zeolite adsorbs CO2 -over-CH4 with a high selectivity (over 1500). The uptake of carbon dioxide is also high (3.31 mmol g −1, 293 K, 101 kPa). This form of zeolite A is a very promising adsorbent for applications such as biogas upgrading, where keeping the adsorption of methane to a minimum is crucial.